Development of a feeding strategy for high cell and PHA density fed-batch fermentation of Ralstonia eutropha H16 from organic acids and their salts. Issue 2 (February 2015) - Huschner, Franz; Grousseau, Estelle; Brigham, Christopher J.; Plassmeier, Jens; Popovic, Milan; Rha, ChoKyun; Sinskey, Anthony J.
Highlights A fed batch fermentation strategy was designed for Ralstonia eutropha using organic acids as feedstock. Organic acids were fed by pH-stat, and organic acid salts were fed using pO2-dependent feed control. A fed batch strategy using three successive carbon/nitrogen ratios (10, 90, to infinite) was employed to maximize PHA productivity. Biomass yield of 112.0 g/L, PHA yield of 93.5 g/L, and a PHA productivity of 2.13 g/L/h was achieved using the strategy outlined in this work.